A new species of Prosopistoma Latreille, 1833 and redescription of P. indicum Peters, 1967 (Ephemeroptera: Prosopistomatidae) from the Western Ghats, India - Roopa, S. Ramya; Selvakumar, C.; Subramanian, K. A.; Sivaramakrishnan, K. G. (Zootaxa, 2017)
Prosopistoma someshwarensis n. sp. is described based on larvae collected from the streams of central Western Ghats, and P. indicum Peters, 1967 is redescribed based on fresh material from additional localities of the southern and central Western Ghats of peninsular India. A brief discussion on their ecology and biogeography, and a key to the Indian species of Prosopistoma, are also provided. The Indian species may be distinguished from one another based on the segmentation of the antennae, carapace colourations, the setation of the tibiae and mandibular canines, and the morphology of gills 2.